Optimasi Terintegrasi Sistem Distribusi Farmasi Menggunakan Klasterisasi Spasial dan Vehicle Routing Problem di Kota Pekanbaru - Puji, Ari Andriyas; Putri, Sunny Ineza; Hermanto, Jheri; Cahyo Prasetyo, Brian Agung; Ulum, Panji (Fakultas Teknik UMRI, 2026)
The availability of essential medicines in primary health facilities remains a chronic issue in many regions due to inefficient distribution systems. This study aims to develop an integrated pharmaceutical distribution model in Pekanbaru City by combining spatial clustering, route optimization, and inventory management. A quantitative approach was employed using GPS coordinates of 21 community health centers (Puskesmas) and 12-month drug consumption data. Analysis involved K-Means Clustering (K=3), Haversine distance calculation, Nearest Neighbor algorithm improved by 2-opt for Vehicle Routing Problem (VRP), and zone-based safety stock and reorder point calculations with a 95% service level. The results identified three distribution zones with a Silhouette Coefficient of 0.5268. The optimal total travel distance was 106.60 km per cycle, representing a 9.08% reduction from the initial solution. Safety stock in Zone C was on average 2.06 times higher than Zone A for Amoxicillin 500 mg. The integration of these components demonstrates a significant improvement in logistics efficiency. This study provides practical recommendations for IFLK Pekanbaru to enhance sustainable medicine availability.